THE IMPLEMENTATION OF PRANATAL EDUCATION IN MAGEDONG-GEDONGAN CEREMONY AT HINDU COMMUNITIES IN URBAN OUTSKIRTS - Jro Ayu Ningrat (Padma Sari: Jurnal Ilmu Pendidikan, 2022)
This article is the result of research that aims to conduct a study of the implementation of the magedong-gedongan ceremony in Hindu communities living in urban outskirts areas focused in Batubulan Village as a form of implementation of prenatal education. The design of this research is descriptive interpretive to interpret the implementation of the magedong-gedongan ceremony associated with the concept of prenatal education. Most of the data taken in this study were in the field, which were then analyzed using interpretive descriptive analysis techniques. This study found that the implementation of the magedong-gedongan ceremony is an obligation that must be carried out as an effort to purify babies who are still in the womb. Although it is an obligation, not all Hindus do it for certain reasons. The implementation of the magedong-gedongan ceremony of the purification process is also a process of prenatal education given to babies who are still in the womb with the hope that after birth they can grow and develop into children who are physically and mentally healthy. Aspects of prenatal education given to the baby who is still in the womb in the form of positive values ​​emitted by the implementation of the magedong-gedongan ceremony which is believed to be accepted by the baby in the womb in forming multiple intelligences.